Revision of the classification of braconidae (1990-2012): Subfamilies in Mexico - Coronado-Blanco, Juana María (Universidad Autónoma de Tamaulipas, 2012)
Braconids are parasitoid wasps used successfully in many biological control programs of insect pests at world level. In this review, the classification of the subfamilies of Braconidae is analyzed because during the last two decades have been noticeable changes, also the genera that change subfamily in this period are recorded. In Mexico, 35 subfamilies are registered (28 in UAT Museum), 318 genera and 704 species. However, there is a great quantity of specimens without identifications in the collections of different universities.